THE UPPERMOST CORROSIVE COMPOSITES IN PETROLEUM OILS AND METALLIC CORROSION - Aluvihara, Suresh; Premachandra, Jagath K. (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2019)
Petroleum oils are the essential compounds in the purposes of industrial mechanisms and a few of other applications since obtaining some adverse impacts from such crude oils on the commonly applicable materials because of the corrosive composites of such crude oils. The investigations of the corrosion rates of seven different types of ferrous metal that applicable in the industry of crude oils refining due to the effects of salts, organic acids, elemental sulfur and Mercaptans of two different types of crude oils were the objectives of the existing research. The chemical compositions of selected ferrous metals, elemental sulfur contents, salt contents, Mercaptans contents and organic acid contents of two different types of crude oils were tested by in order of XRF detector, XRF analyzer, salt analyzer and titration methods. A bath of prepared seven different types of metal coupons was dipped in both crude oils samples separately and homogeneously. In order of after 15, 30 and 45 days from the immersion the corrosion rates of such metal coupons were determined by the weight loss method with the aid of the qualitative microscopic analysis of the corrosion. According to the results that there were obtained the lower corrosion rates from stainless steels especially with the chemical composition at least 12% of chromium with sufficient amount of nickel because of the self corrosion protection film of such metals, relatively higher impact from salts on the metallic corrosion, formations of FeS, Fe2O3, corrosion cracks and irregular pitting on the metal surfaces.